A ninety-six well plate as headspaces with moist starch indicator paper as a cover for the determination of ascorbic acid by iodate oxidation and formation of volatile iodine - Thichaphat Nawalohakul; Pannarat Charoenjiraroj; Rattikan Chantiwas; Prapin Wilairat; Wiboon Praditweangkum (Analytical Methods, 2022)
= 0.05).
Keywords: Analytical Chemistry and Sensors; Vitamin C and Antioxidants Research; Advanced Chemical Sensor Technologies